Strigolactone signaling regulates specialized metabolism in tobacco stems and interactions with stem-feeding herbivores. - Suhua Li; Youngsung Joo; Dechang Cao; Ran Li; Gisuk Lee; Rayko Halitschke; Gundega Baldwin; Ian T Baldwin; Ming Wang (PLoS Biology, 2020)
Plants are attacked by herbivores, which often specialize on different tissues, and in response, have evolved sophisticated resistance strategies that involve different types of chemical defenses frequently targeted to different tissues. Most known phytohormones have been implicated in regulating these defenses, with jasmonates (JAs) playing a pivotal role in complex regulatory networks of signaling interactions, often generically referred to as "cross talk." The newly identified class of phytohormones, strigolactones (SLs), known to regulate the shoot architecture, remain unstudied with regard to plant-herbivore interactions. We explored the role of SL signaling in resistance to a specialist weevil (Trichobaris mucorea) herbivore of the native tobacco, Nicotiana attenuata, that attacks the root-shoot junction (RSJ), the part of the plant most strongly influenced by alterations in SL signaling (increased branching). As SL signaling shares molecular components, such as the core F-box protein MORE AXILLARY GROWTH 2 (MAX2), with another new class of phytohormones, the karrikins (KARs), which promote seed germination and seedling growth, we generated transformed lines, individually silenced in the expression of NaMAX2, DWARF 14 (NaD14: the receptor for SL) and CAROTENOID CLEAVAGE DIOXYGENASE 7 (NaCCD7: a key enzyme in SL biosynthesis), and KARRIKIN INSENSITIVE 2 (NaKAI2: the KAR receptor). The mature stems of all transgenic lines impaired in the SL, but not the KAR signaling pathway, overaccumulated anthocyanins, as did the stems of plants attacked by the larvae of weevil, which burrow into the RSJs to feed on the pith of N. attenuata stems. T. mucorea larvae grew larger in the plants silenced in the SL pathway, but again, not in the KAI2-silenced plants. These phenotypes were associated with elevated JA and auxin (indole-3-acetic acid [IAA]) levels and significant changes in the accumulation of defensive compounds, including phenolamides and nicotine. The overaccumulation of phenolamides and anthocyanins in the SL pathway-silenced plants likely resulted from antagonism between the SL and JA pathway in N. attenuata. We show that the repressors of SL signaling, suppressor of max2-like (NaSMXL6/7), and JA signaling, jasmonate zim-domain (NaJAZs), physically interact, promoting NaJAZb degradation and releasing JASMONATE INSENSITIVE 1 (JIN1/MYC2) (NaMYC2), a critical transcription factor promoting JA responses. However, the increased performance of T. mucorea larvae resulted from lower pith nicotine levels, which were inhibited by increased IAA levels in SL pathway-silenced plants. This inference was confirmed by decapitation and auxin transport inhibitor treatments that decreased pith IAA and increased nicotine levels. In summary, SL signaling tunes specific sectors of specialized metabolism in stems, such as phenylpropanoid and nicotine biosynthesis, by tailoring the cross talk among phytohormones, including JA and IAA, to mediate herbivore resistance of stems. The metabolic consequences of the interplay of SL, JA, and IAA signaling revealed here could provide a mechanism for the commonly observed pattern of herbivore tolerance/resistance trade-offs.